الصورة الوالدية عند المراهق المدمن - قواري, سعاد (كلية العلوم الاجتماعية, 2019)
الملخص: تضمنت الدراسة معرفة الصورة الوالدية التي يدركها المراهق المدمن على التدخين والكوكايين والايريكا ومعرفة هذه الصورة التي يكونها عن أمه إذا كانت سلبية ومعرفة هل الصورة التي يكونها المراهق المدمن عن أبيه إذا كانت سلبية؟. وتمت هذه الدراسة مع فئة المراهقين المدمنين على التدخين والكوكايين والايريكا والذين يتبعون العلاج بمركز الوسيط لعلاج المدمنين بمستغانم، تتراوح أعمارهم (من 71الى 02سنة) وذلك في الدراسة الأساسية في حيث قمت مع كل حالة خمس مقابلات ومقابلتين في تطبيق الاختبار كما استعملت الاختبارات النفسية والاختبارات الاسقاطية منها اختبار تفهم العائلة ( )FATواختبار رسم العائلة. وقد استعملت في هذه الدراسة المنهج الاكلينيكي الموضوع يتطلب دراسة الحالة والمقابلة العيادية والملاحظة العيادية وكشفت الدراسة عن: 7ـ يكون المراهق المدمن صورة سلبية عن أمه. 0ـ يكون المراهق المدمن صورة سلبية عن أبيه. وتشير إلى أن النتائج غير قابلة للتعميم وهذا حسب الاهداف المسطرة للبحث ونظرا للصعوبات التي واجهتها في ضبط كل المتغيرات لانتقاء عينة الدراسة وتتمثل في: ـ معرفة الصورة التي يكونها عن أبيه السلبية. ـ معرفة الصورة التي يكونها عن أمه السلبية. ـ اقتراح دراسة الموضوع بالمنهج الوصفي.ث -محاولة معرفة اهم الاسباب التي تدفع المراهق للجوء الى بوابة الادمان . ـ الكشف عن أهم المشاكل التي يعانيها المراهق المدمن اتجاه والديه. وقد ختمنا الدراسة بجملة من الاقتراحات على ضوء النتائج المتحصل عليها.ث Abstract This study deals with the adolescent category, more precisely; the teenager who is addicted to smoking, cocaine and Erica, and the way he sees his parents. It aims at knowing whether the picture he/she has about both of their mother and father is negative or not ? The research was conducted with addicts adolescents ; smoking, cocaine and Erica, who were treated at the Mostaganem Treatement Center for Addicts, between the age of 17 and 20 years. In each case, I conducted five interviews and two interviews in the application of the test. I relied on both of the psychological and probative tests Including the family understanding (FAT) and family drawing tests. I adobted the clinical approach That requires a case study, a clinical interview and a clinical observation. The study révèle: The addicted teenager develops à negative image towards his mother. The addicted teenager develops a negative image towards his father. The data collected indicate that the results cannot be subjected to generalization due to the objectives of the search and some given difficulties encountered in the control of all variables to select the sample of the study, they are represented in: Knowing the negative image that the teenager has about his/her mother. Knowing the negative image that the teenager has about his/her father. Trying to acquire as much theoretical and applied information as possible. A proposal to study the subject from a descriptive approach.ث Detecting the most important reasons that lead the teenager to resort to addiction. Detecting the most important problems experienced by an addicted teenager towards his/her parents. The study is concluded with a series of suggestions in the light of the results obtained
دراسة ميدانية لأربع حالات مدمنين على التدخين و الكوكايين و الإريكا بمركز الوسيط لعلاج المدمنين بمستغانم
Keywords: المراهقة؛الادمان؛المخدرات؛التدخين؛الكوكايين؛الايريكا؛الصورة الوالدية؛